Short term results comparison of antibiotic resistance in COPD patients with exacerbation (Annals of Medical Research, 2021)
Aim: To obtain data which could be of guidance in the selection of empirical antibiotic treatment through bacteria isolation from sputum and antibiotic sensitivity tests in patients hospitalised because of exacerbation of chronic obstructive pulmonary disease (COPD).Materials and Methods: Sputum samples were induced before antibiotherapy in patients hospitalised because of COPD exacerbation. In addition to routine tests and infection markers, sputum cultures and antibiotic resistance tests were applied. Results: The study included 101 patients. Production was determined in the sputum cultures of 28 (27.7%) patients. In the group with bacteria isolated in the sputum, there was determined to be a high number of exacerbations in the last year, partial oxygen pressure (PaO2) was low, and procalcitonin (PCT), the neutrophil ratio, white blood cell count (WBC) and the modified Medical Research Council Dyspnea Score (mMRC) were found to be higher than in the patients with negative sputum (p